2018
DOI: 10.1155/2018/5962153
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution in Chroming Coatings Friction Pairs under Dry Sliding Test Conditions

Abstract: The microstructures of subsurface layers of 20CrMnTi steel pins against chroming and nonchroming T10 under dry sliding tests were studied by means of OM (optical microscopy), XRD (X-ray diffraction), and SEM (scanning electron microscopy). Results showed that the chroming coating strengthened the disc surface and significantly affected microstructural evolution. Three layers-the matrix, deformation layer (DL), and surface layer (SL)-formed in 20CrMnTi for the chroming T10. The matrix and deformation layer (DL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…The high initial COF value for all conditions was due to the adhesion wear that occurred between the coated samples and the ball. Also, it is important to point out that the coefficient of friction values obtained in this study showed values lower than values obtained from Cr coatings by previous researchers [ [40] , [41] , [42] , [43] ], which invariably connotes better wear resistance. This signifies an improved adhesion of the electrodeposited Cr coating to the SS substrate, and this improvement could be attributed to the new pretreatment method (anodic activation) developed in this study.…”
Section: Resultscontrasting
confidence: 64%
“…The high initial COF value for all conditions was due to the adhesion wear that occurred between the coated samples and the ball. Also, it is important to point out that the coefficient of friction values obtained in this study showed values lower than values obtained from Cr coatings by previous researchers [ [40] , [41] , [42] , [43] ], which invariably connotes better wear resistance. This signifies an improved adhesion of the electrodeposited Cr coating to the SS substrate, and this improvement could be attributed to the new pretreatment method (anodic activation) developed in this study.…”
Section: Resultscontrasting
confidence: 64%
“…Therefore, traditional approaches are used to increase the reliability and service life of such units. These include selecting a material combination for the parts of the friction pairs, using various chemical and thermal technologies for processing friction surfaces, and applying various effective coatings through various physico-chemical methods [2,3].…”
Section: Introductionmentioning
confidence: 99%